(untitled) (American & British Studies Annual, 2015)
The paper focuses on the multiplicity of spaces structuring the novel Daniel Deronda and attempts to demonstrate an understanding of space projected by George Eliot in the European context. This last novel of George Eliot was in this respect more revelatory than her previous works, as it moves the author’s perception of space far from English regionalism. The paper further contrasts the use of space in Daniel Deronda with Eliot’s previous novels using Deleuzoguattarian smooth and striated space as well as certain Romantic impulses in Victorian novels as defined by D. D. Stone. A significant aspect of the study is an analysis of water as space, namely interpreting the presence of the River Thames and the sea along the port of Genoa. Both of these water spaces contribute greatly to the development of the novel’s plot towards a tragic mood. Heidegger’s philosophical treatment of the spatial aspect of the bridge will be focused upon in the final part of the article.